Sleep during the third trimester of pregnancy: the role of depression and anxiety - Ruiz-Robedillo, N. (2015)
Depression has been associated with sleep disturbances in pregnancy; however, no previous research has controlled the possible confounding effect of anxiety on this association. This study aims to analyze the effect of depression on sleep during the third trimester of pregnancy controlling for anxiety. The sample was composed by 143 depressed (n = 77) and non-depressed (n = 66) pregnant women who completed measures of depression, anxiety, and sleep. Differences between groups in sleep controlling for anxiety were found. Depressed pregnant women present higher number of nocturnal awakenings and spent more hours trying falling asleep during the night and the entire 24 h period. Present findings point out the effect of depression on sleep in late pregnancy, after controlling for anxiety.